Evaluasi Kuat Tekan Beton Terpasang pada Struktur Dermaga Eksisting Berdasarkan Pengujian Destructive dan Non-Destructive - Herdiansah, Yudi; Cendana, Widhi Prima (Jurnal Teknik Sipil, 2025)
The dock is a critical component of a port, serving both as a mooring facility and a berthing area for ships. Given the importance of the quay, it is essential to ensure that each quay is equipped with suitable and functional facilities, both in terms of operational use and structural integrity. One method of evaluating existing quays is through structural testing. The objective of this structural testing is to obtain material parameters that will serve as inputs for modeling the existing structure. The material testing parameters to be determined include equivalent concrete compressive strength values, which will be used as references in the structural modeling of the quay. The structural testing comprises both destructive (DT) and non-destructive tests (NDT). To achieve results that accurately represent the overall condition of the existing structure, each test must be correlated with others. The correlations analyzed include those between core drill tests and hammer tests, as well as between core drill tests and ultrasonic pulse velocity (UPV) tests. The correlation results chosen for use in the structural modeling are those between core drill tests and UPV tests. The equivalent compressive strength values obtained from this analysis are 21.41 MPa for Segment 1, 24.1 MPa for Segment 2, and 23.18 MPa for Segment 3. The analysis reveals differences in the equivalent compressive strength values for each segment, likely due to variations in the construction years of the quay segments, which correspond with the observed differences in equivalent concrete compressive strength.